Solutions and Stability of Generalized Mixed Type QC Functional Equations in Random Normed Spaces - Gordji MadjidEshaghi; Zolfaghari Somaye; Cho YeolJe (Journal of Inequalities and Applications, 2010)
We achieve the general solution and the generalized stability result for the following functional equation in random normed spaces (in the sense of Sherstnev) under arbitrary t-norms: , where for any fixed integer with .